Anthropometric proportions of pregnant women establishing safe and ergonomic dimensions based on comfort-requirement - Narvaez, Nory Loyd P. (2007)
There are approximately 1,000,000 women pregnant at one time. In Davao City, there are approximately 33,000 pregnant women from January to December 2005. the magnitude of their population is a crucial concern in the provision for health, safety, sanitation, and hygiene. Pregnancy is a state of becoming: an unborn baby is becoming a person capable of life outside the safe, protective and totally sufficient environment of the mother's body, and a man and woman becoming parents. Pregnancy is a positive growth experience for most expectant parents. It is a time to draw on or develop a support system, to assess one's lifestyle and make changes if necessary to ensure optimal health. This study aims to uplift and assist in the provision of good health through specifying and knowing measures of comfort, safety and convenience for the pregnant mother. These measures include material comfort, physiological comfort, bio-mechanical comfort, and technological comfort but as an emphasis the study focused on the structural anthropometrics of pregnant women. A total of thirty three body measurements are obtained from 120 pregnant women, 40 in each trimester. Also, to distinguish user responses to the external environment motion study, study of reach, activity analysis, and present condition assessment were performed. Considerable difference in measurements signified the apparent changes in the body of the pregnant women. Measurements, such as weight and width of abdomen show the most effect of the pregnancy condition. The different user needs, preferences and perceptions on their environment were reflected in the recommendations for spatial provision, furniture design, equipment provision, activity management and material specification. The pregnancy experience is defined by relationships, finances, physique, emotion, responsibility, time and environment. However, there is no universal agreement among medical professionals or the general public on the single best, safest, and most comfortable way to experience pregnancy. But to a great extent the kind of pregnancy experience a woman could have will largely depend on the care and provisions available. The results were used to formulate guidelines for the design of maternity hospital. This facility was aimed at providing comfort through the application of three (3) interventions namely educational, physical, and medical intervention. This integrative approach aim at holistically address the needs of pregnant women for comfort. The project is located along J.P. Cabaguio Avenue, fronting the Davao Medical Center.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2007